2016
DOI: 10.1016/j.anbehav.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Courtship and male ornaments as honest indicators of immune function

Abstract: Having an effective immune system can be very costly, sometimes at the expense of other important life history traits, including reproduction. This tradeoff can be exaggerated in males of species that have costly sexual signaling, where conditiondependent components of the signaling system reflect the health status of the bearer. It is therefore vital for a male to be able to adequately balance the costs of activating the immune system successfully while also expressing high quality sexual signals. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 55 publications
1
23
1
1
Order By: Relevance
“…However, these results suggest that females are able to detect a male's current health status via cuticle‐based chemical compounds and are less likely to show receptivity to a male that has consumed a bacterial pathogen recently. This is particularly interesting given that in live mating trials, females do not discriminate against males who are infected with the same pathogen at the same dose (Gilbert & Uetz, ). This could be because females may evaluate sexual signals differently, and can possibly gather important information about male quality from one signaling modality that outweighs information within another signaling modality.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, these results suggest that females are able to detect a male's current health status via cuticle‐based chemical compounds and are less likely to show receptivity to a male that has consumed a bacterial pathogen recently. This is particularly interesting given that in live mating trials, females do not discriminate against males who are infected with the same pathogen at the same dose (Gilbert & Uetz, ). This could be because females may evaluate sexual signals differently, and can possibly gather important information about male quality from one signaling modality that outweighs information within another signaling modality.…”
Section: Discussionmentioning
confidence: 99%
“…One week after molting to sexual maturity, males were infected with the bacterial pathogen Pseudomonas aeruginosa strain PA‐14. This pathogen has been used successfully in previous studies to elicit an immune response (Gilbert et al, ; Gilbert & Uetz, ) and has been found in individuals that were sequenced using 16s rRNA primers (R. Gilbert, unpublished data). Stocks were kept at −80°C in Copan Cryovials and grown 18 hr before experiments on Luria broth media (1.0% Tryptone, 0.5% yeast extract, 1.0% NaCl, 1.5% agar).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations